Growth and Fruit Chemical Characteristics of Blackberry (Rubus Fruticosus) Cultivated with Vermicompost, Glomus Mosseae and Phosphate Rock. Issue 4 (2nd October 2018) - Abud-Archila, Miguel; Luján-Hidalgo, María Celina; López-Pérez, Jaeni Mibeth; Ordaz-Rivera, Josué; Ruiz-Valdiviezo, Víctor Manuel; Oliva-Llaven, María Ángela; Gutiérrez-Miceli, Federico Antonio
Abstract: The aim of this investigation was to determine the effect of vermicompost (V) and phosphate rock (PR) on blackberry (Rubus fruticosus L. agg.) plants inoculated with Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe (AMF). Plant growth parameters, total phenol compounds and total flavonoids were evaluated on leaves. Anthocyanin contents, soluble solids (SS), pH, titratable acidity (TA) and SS/TA ratio was evaluated in blackberries fruits. Blackberry plants were obtained from cuttings from field plants, which were distributed in soil according to a randomized complete block design with three repetitions. Treatments were vermicompost (10░g plant −1 ), phosphate rock (1░g plant −1 ), Glomus mosseae (AMF), (1░g plant −1 ), PR + AMF, V + PR, V +AMF, V + PR+ AMF and control without any amended. Plant height and stem diameter were measured five months after treatments, while total phenols and total flavonoids in leaves were evaluated eight months later. Anthocyanins, SS, pH, and TA were determined in blackberry fruits ten months after. Plant height was not statistically affected (p≤0.05), although total phenol compounds were higher (21.1░mg g −1 dry plant) in the V+PR+AMF treatment, whereas the V + AMF treatment produced more dry plant total flavonoids (1.4░mg g −1 ), compared with control plants. Blackberries produced with the vermicompost treatment had more anthocyanins (9.54░mg g −1 ) than control plants. Soluble solids, pH and titratable acidity were not statistically (p≤0.05) affected by any treatment.